The Effect of Perceived Career Plateau on Career Anchor in Modern Workforce - UYSAL, Assoc. Prof. H.Tezcan; AK, Asst.Prof. Murat (The journal of contemporary issues in business and government, 2021)
The aim of this study is to examine whether there is a meaningful relationship between career plateaus, and employees and their gradually developed career anchors. A career plateau is defined as the point at which the possibility for an employee to progress in their career is at the lowest. A career anchor refers to the needs, values, and abilities which shape an individual’s career decisions (Jiang & Klein, 2000). This study also aims to determine if a career plateau affects employees’ career anchors. A negative and statistically significant relationship was observed between a career plateau and a career anchor. It was revealed that 22.1% of the change in the employees’ career anchors was explained by improvements to their career plateaus. It was found that a 1-unit increase in a career plateau perception caused a career anchor to decrease by 1.860 units.